Blow up of classical solutions to the isentropic compressible Navier–Stokes equations. (October 2015) - Lai, Ning-An
Abstract: In this work we consider the isentropic compressible Navier–Stokes equations in three space dimensions. Blow up result will be established, assuming the gradient of the velocity satisfies some decay constraint and the initial total momentum does not vanish. We prove the main result by a contradiction argument, based on the conservation of the total mass and the total momentum.